Systematic study of the chiral smectic phases of a fluorinated compound. Issue 15 (8th December 2019) - Lalik, S.; Deptuch, A.; Fryń, P.; Jaworska–Gołąb, T.; Dardas, D.; Pociecha, D.; Urbańska, M.; Tykarska, M.; Marzec, M.
ABSTRACT: Physical properties of the partially fluorinated compound 3F5FPhF, with hockey stick-like molecules, were studied by complementary methods. Apart from the already reported paraelectric SmA*, ferroelectric SmC* and antiferroelectric SmC*A phases, the presence of the smectic C*α subphase in the phase sequence was proved by differential scanning calorimetry, polarising optical microscopy, electro-optic and dielectric spectroscopy methods. The temperature dependence of the smectic layer thickness and correlation length of the lateral short-range order was determined by X-ray diffraction. Based on dielectric measurements three relaxation processes were revealed in the antiferroelectric SmC*A phase (two collective: PL, PH and one molecular: s-process), two collective ones (Goldstone and soft modes) were found both in the ferroelectric SmC* phase and SmC*α subphase while one relaxation process (soft mode) in the paraelectric SmA* phase. The results were compared with that obtained for other structurally similar compounds, and it was shown that even addition of one methylene group to the side chain influences much on the physical properties. Abstract :